The AAC Mentor Project: Web-based instruction in sociorelational skills and collaborative problem solving for adults who use augmentative and alternative communication. - Light, Janice; McNaughton, David; Krezman, Carole; Williams, Michael; Gulens, Maija; Galskoy, Alix; Umpleby, Marleah (AAC: Augmentative & Alternative Communication, 2007)
In this study, we investigated the effects of a self-paced instructional program, delivered via an accessible website, to teach sociorelational skills and collaborative problem-solving skills to adults with cerebral palsy who used augmentative and alternative communication (AAC). The instruction was designed to prepare participants to serve as mentors, in an Internet-based mentor program, for adolescents and young adults who also used AAC (Light & McNaughton, 2002). The effect of the training program was evaluated in two separate studies utilizing single-subject multiple probe designs: Study 1 investigated the effects of Lesson 1 of the web-based instructional program on the acquisition of sociorelational skills by six adults who used AAC; and, Study 2 focused on the effects of Lesson 2 on the acquisition of collaborative problem-solving skills by 15 adults who used AAC. All participants in Study 1 successfully acquired the target sociorelational skills to help them establish positive mentoring relationships with their protégés, and all participants in Study 2 acquired the collaborative problem-solving skills to support protégés in overcoming challenges in their lives and attaining goals. Results are discussed, along with implications for practice and directions for future research.